Phonon Driven Ferroelectricity and Raman Active Modes in Hybrid Organic-Inorganic Perovskites - Li, Chuanzhao (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.